Analisis Faktor-Faktor Yang Mempengaruhi Prinsip Prudence Akuntansi Pada Perusahaan Sektor Finansial Yang Tercatat Di Bursa Efek Indonesia tahun 2020-2022 - Windiani, Titik; Ananto, Rangga Putra; Ferdawati (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This research aims to determine the effect of independent commissioners, institutional ownership, audit quality, litigation risk, capital intensity, fair value intensity, profitability and company size on prudence accounting. Population in this study is the financial sector listed on the Indonesia Stock Exchange in 2020-2022. Purposive sampling method was used to determine the research sample so that a sample of 193 observations was obtained. Hypothesis testing using multiple linear regression analysis. The data is processed using the SPSS v.25 application. The results showed that litigation risk, capital intensity and profitability affect accounting prudence. Independent commissioners, institutional ownership, audit quality, fair value intensity and company size have no effect on accounting prudence. Simultaneously, independent commissioners, institutional ownership, audit quality, litigation risk, capital intensity, fair value intensity, profitability and company size affect prudence accounting.